2018
DOI: 10.18632/oncotarget.26051
|View full text |Cite
|
Sign up to set email alerts
|

Role of textural heterogeneity parameters in patient selection for 177Lu-PSMA therapy via response prediction

Abstract: PurposeProstate cancer is most common tumor in men causing significant patient mortality and morbidity. In newer diagnostic/therapeutic agents PSMA linked ones are specifically important. Analysis of textural heterogeneity parameters is associated with determination of innately aggressive and therapy resistant cell lines thus emphasizing their importance in therapy planning. The objective of current study was to assess predictive ability of tumor textural heterogeneity parameters from baseline 68Ga-PSMA PET pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 29 publications
3
34
0
Order By: Relevance
“…This observation of MX response underlines the well-known development of heterogeneity of PC lesions over time. Textural heterogeneity parameters may also play an important role explaining these findings [14]. In fact, all our patients with MX response also showed increasing PSA values over time und thus disease progression.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…This observation of MX response underlines the well-known development of heterogeneity of PC lesions over time. Textural heterogeneity parameters may also play an important role explaining these findings [14]. In fact, all our patients with MX response also showed increasing PSA values over time und thus disease progression.…”
Section: Discussionmentioning
confidence: 58%
“…In 8 patients (nos. 1,3,6,7,8,14,20,32), bone-targeted therapy was continued after 177 Lu-PSMA-617 therapy had commenced. and could be discharged 48 h post-injection.…”
Section: Patient Selectionmentioning
confidence: 99%
“…In several previous studies the ability of textural parameters assessed in PET/CT examination as surrogate marker for tumor heterogeneity to predict treatment outcome was shown [12,[19][20][21]. Especially higher-order textural features correlate well with the human perception of texture and shape of s structure and reflect therefore the impression of the physician [22].…”
Section: Discussionmentioning
confidence: 92%
“…As a result, it would be possible to exclude non-responders from this treatment to avoid undesirable side effects and cost-intensive treatments without benefit for the individual patient. In this context, Khurshid et al reported a significant correlation between some textural parameters such as the mean homogeneity and entropy in 68 Ga-PSMA-PET scans and response to 177 Lu-PSMA therapy as determined by the reduction of prostate-specific antigen (PSA) levels [ 24 ]. Development of an ML algorithm for therapy decision would be of high interest for general oncology and for the selection of patients for clinical trials and could be an important further step towards individualized tumor therapy.…”
Section: Discussionmentioning
confidence: 99%